Cana-de-açúcar em bacias hidrográficas experimentais irrigadas - Silva, Vanessa Lorencini da [UNESP] (2014)
Understanding the spatial distribution of crops, based on topographic information, can provide opportunities for specific management applications. With this work is aimed to quantify the effect of the exposure, slope and irrigation influence on the production of second cut of sugar cane. The research was developed in the experimental area of the Department of Agricultural Engineering of FCAV / UNESP, called Experimental Hydrographic Basins with areas of 10.5 m², two in the horizontal and the other with a gradient of 10, 20, 30, 40 and 50% and exhibitions north, south, east and west. Drip irrigation was performed on all surfaces, except in a horizontal. The variety used was the RB855453. At harvest were analyzed the masses of the stems, number of tillers, productivity, total recoverable sugar (ATR in Portuguese) and fiber. The production of sugar cane was affected by exposure, being favored in western exposure. The greatest yields occurred in W10, W20 and W40 surfaces